An Adaptation and Validation of The Indonesian Version of The Bullying and Cyberbullying Scale for Adolescents - Fauzan Heru Santhoso; Ramadhan Dwi Marvianto; Budi Purwanto (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Measurement of bullying behaviour in the Indonesian context has not received much attention let alone a comprehensive measurement of bullying which includes all forms of bullying and the role of individual both as perpetrator and victim. The Bullying and Cyberbullying Scale for Adolescents (BCS-A) developed by Thomas and his colleagues has comprehensive coverage and measures individuals either as perpetrator or victim. The purpose of this study was to adapt and test the psychometric properties of the Indonesian version of the BCS-A scale. This research included two stages: the first stage was adapting the scale from English to Bahasa Indonesia using Beaton’s guideline, while the second stage was validating the Indonesian version of the BCS-A scale. The subjects of this study were 330 high school students in the Special Region of Yogyakarta who participated in the study by completing the BCS-A questionnaire through online surveys. The result of the adaptation stage, that is the Indonesian version of the BCS-A scale, was supported by an evidence of validity based on subject response. At the validation stage, the Indonesian version of the BCS-A was found to have a good validity based on internal structure and satisfactory reliability.